Apparent asystole: are we missing a lifesaving opportunity?. (16th March 2015) - Limb, Christopher; Siddiqui, Muhammad A
Abstract : The use of ultrasonography is rapidly expanding in emergency medicine. Real-time assessment offers clues to prompt diagnosis and creates opportunities for speedy intervention. We present a case of 'cardiac monitor asystole' that proved to be ventricular fibrillation on ultrasound examination. Uniquely this case demonstrates that this, typically unrecognised, form of ventricular fibrillation responds to desynchronised defibrillation, with restoration of perfusion for approximately 30 min. With increasing access to ultrasound we believe that further research is indicated to determine whether some cases of apparent asystole may best be treated by defibrillation, presenting an opportunity to save more lives than current protocols achieve.